Phosphorus-modified Zr-based metal-organic framework materials for their effective removal of thorium from aqueous solutions - Yinghao Zhuang; Shuai Sun; Kai Jia; Lei Shi; Xiangshan Yang (Adsorption Science & Technology)
Thorium is a promising nuclear fuel; however, even a small amount in nuclear wastewater can cause significant radioactive pollution. Therefore, it is urgent to develop effective adsorbents for the efficient removal of thorium to solve this problem. Herein, the phytic acid modification of carboxylated Zirconium-based metal-organic framework materials (UiO-66-COOH-PA) has been obtained by rapid high-temperature carbonization, which exhibits excellent performance in removing thorium (IV) in acidic aqueous solutions. The maximum adsorption capacity of UiO-66-COOH-PA-2 (with 40% mass ratio of phytic acid) in solution reaches 315.5 mg/g at a pH of 4, which is more than twice that of the unmodified Zr-based metal organic framework (MOF) material. The adsorption kinetics of UiO-66-COOH-PA on thorium has been analyzed using two different isothermal adsorption models, the Langmuir and Freundlich isotherm adsorption models. It turns out that the Freundlich model is more suitable for the data. The thorium adsorption process reaches dynamic equilibrium very quickly, while the adsorption dynamics of UiO-66-COOH-PA on thorium follows the pseudo-second-order adsorption kinetic model. The excellent adsorption performance of UiO-66-COOH-PA-2 at low pH values indicates that adsorption material containing phosphorus is suitable for the removal of thorium especially in acidic systems. It also exhibits excellent selectivity (up to 90.2%) for Th(IV) adsorption in the presence of several coexisting rare-earth ions. Overall, the integration of phosphorus-modified in Zr-MOFs represents a significant advancement in thorium adsorption technology, offering a pathway toward more effective management of radioactive acidic waste liquid.